Perceptions of rural primary healthcare personnel about expansion of early communication intervention - Jeannie van der Linde; Alta Kritzinger (AOSIS, 2013)
Background: Early communication intervention services rendered by speech-language therapists and audiologists to families of infants and young children with feeding difficulties, hearing loss or emerging communication disorders should be implemented throughout South Africa. Early intervention can ameliorate risks, enhance development and may prevent further delays. Based on research initiated during a community-service year experience in a rural subdistrict,an incremental process of establishing accessible early communication intervention services was deemed feasible. Such a process cannot be successful if the collaboration of primary healthcare personnel and managers is not ensured. Objectives: The aim of the article was to describe the perceptions of primary healthcare personnel with regard to expansion of early communication intervention services to infants at risk of developmental delay. Method: A qualitative descriptive survey design was followed. Semi-structured interviews were conducted with 20 primary healthcare nurses and sisters and eight primary healthcare programme managers in Ditsobotla subdistrict in the North West province of South Africa. Results: The participants indicated that by improving team work, developing training programmes and evaluating identification methods and resources, the step-by-step rollout of early communication intervention functions on four organisational levels may be a realistic goal for sustainable services in the resource-limited district. Conclusion: The positive perceptions and contributions by participants promise a rich human-resource basis for transdisciplinary collaboration between speech-language therapists, audiologists and primary healthcare personnel in order to reduce the burden of early communication disorders in a rural district.